2022
DOI: 10.3389/fnut.2022.843832
|View full text |Cite
|
Sign up to set email alerts
|

Create Fat Substitute From Soybean Protein Isolate/Konjac Glucomannan: The Impact of the Protein and Polysaccharide Concentrations Formulations

Abstract: In this study, soybean protein isolate (SPI) and coconut oil were emulsified and konjac flour was added to prepare the protein/polysaccharide composite emulsion gel. The SPI/polysaccharide compound fat substitute was obtained by vacuuming. The effects of protein and konjac flour addition on the gel system of the mixed emulsion were explored. Sensory evaluation experiments showed that the overall acceptability of fat substitutes added with 1% SPI was higher. With the increase of protein and konjac content, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 42 publications
(43 reference statements)
3
16
0
Order By: Relevance
“…In addition, several studies [12,[44][45][46] explored the effect of the protein content on plant-based emulsified cross-linked fat crystal networks simulating animal adipose tissue, confirming that the textural and rheological properties of emulsion gels can be changed to some extent by modifying the protein content in the initial emulsion before TG cross-linking.…”
Section: Protein-based Emulsion Gels As Fat Substitutes In Meat Productsmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, several studies [12,[44][45][46] explored the effect of the protein content on plant-based emulsified cross-linked fat crystal networks simulating animal adipose tissue, confirming that the textural and rheological properties of emulsion gels can be changed to some extent by modifying the protein content in the initial emulsion before TG cross-linking.…”
Section: Protein-based Emulsion Gels As Fat Substitutes In Meat Productsmentioning
confidence: 87%
“…This change is beneficial to the formation of the 3D cube fat substitute, modifying the textural properties and gel network structures of emulsion gels by adjusting the number of added polysaccharides and proteins, facilitating customization to obtain the optimal emulsion gel structure. Huang et al [46] used an aqueous SPI solution homogenized with coconut oil to prepare an emulsion and subsequently added konjac glucomannan to obtain a 3D cube emulsion gel with a certain hardness and strength via the TG cross-linking effect. This was used as a fat substitute to study the effect of adding different protein and konjac concentrations to the emulsion gel systems.…”
Section: Protein-polysaccharide Composite-based Emulsion Gels As Fat ...mentioning
confidence: 99%
“…The rheological experiments were performed according to a method delineated by Huang et al with minor modifications [ 44 ]. The emulsion of the plant-based pork rind was heated at 95 °C and stirred at 4000 rpm for 5 min in a cooking machine (Vorwerk, TM5, Vorwerk, Wuppertal, Germany) and cooled to room temperature (25 °C) before measurement.…”
Section: Methodsmentioning
confidence: 99%
“…After heating, the viscosity increases significantly, which is conducive to improving the texture and juiciness of simulated fat, which makes it a popular binder for the formulation of simulated fat in plant-based hamburger [ 92 ]. Huang et al [ 93 ] found that the addition of 4% konjac glucomannan to solid block simulated fat with soybean protein and coconut oil as the main ingredients resulted in a similar appearance to pork fats, with more desirable functional properties in terms of mechanical properties and oral tribology, and better chewiness and mouthfeel scores.…”
Section: Factors Affecting the Structural Quality Of Simulated Fatmentioning
confidence: 99%
“…The simulated fat helps to refine the structure of the recombinant plant-based meat alternatives to adequately mimic the taste of animal meat products. It has been demonstrated that by optimizing the formulation, block simulated fat with sensory properties similar to pork fat, such as hardness, flexibility and chewiness, can be created for the assembly of reconstituted plant-based meat alternatives with improved sensory qualities [ 93 ]. Simulated fat has favorable water and oil-holding properties, and may, thus, provide recombinant plant-based meat alternatives with a delicate and juicy feel, maximizing the bonding effect, and facilitating assembly and molding.…”
Section: Factors Affecting the Overall Structural Quality Of Recombin...mentioning
confidence: 99%